2017
DOI: 10.2298/zipi1701117j
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of a special educational institution to a more inclusive society

Abstract: Despite the fact that the integration model of education was introduced in Slovenia 17 years ago, the inclusion of persons with special needs into education and community remains a major challenge. In order to improve their opportunities, the largest special school in Ljubljana has for ten years organised an international festival Play with me, with the main aim of supporting inclusion of people with special needs with the rest of the population. The organisers aim to create opportunities for all to take part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…They showed the highest degree of agreement with the statement Special educational institutions (e.g. elementary schools with lower performance criteria, special education departments, sheltered work centres) also make an important contribution to an inclusive community, as already shown by a previous piece of research (Jeznik, Mažgon & Ermenc, 2017). They also supported the statement I believe that people from mainstream preschools/schools/society would accept a person with special needs (over 88%).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…They showed the highest degree of agreement with the statement Special educational institutions (e.g. elementary schools with lower performance criteria, special education departments, sheltered work centres) also make an important contribution to an inclusive community, as already shown by a previous piece of research (Jeznik, Mažgon & Ermenc, 2017). They also supported the statement I believe that people from mainstream preschools/schools/society would accept a person with special needs (over 88%).…”
Section: Discussionsupporting
confidence: 71%
“…The Act may be said to reflect the narrow understanding of inclusion because it prescribes procedures that derive from diagnosis of a child's deficits, which are the basis for the inclusion of a student in the appropriate programme and includes a determination of the interventions to be carried out by the appropriate special pedagogical personnel. Moreover, as it was already shown (Jeznik, Mažgon & Ermenc, 2017;Šelih, 2015), while the Act does allow the enrolment of children with mild intellectual disability in mainstream schools, and thus also the integration of standard and adapted programmes, this practice has not taken off because the basic conditions for the coordination of two or more programmes within a single class have not been met.…”
Section: The Slovenian Approach To Realising a More Inclusive Educatimentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation might be that inclusion is more an issue of attitude than an issue of knowledge. We came to a similar conclusion in another piece of research (Jeznik, Mažgon, & Ermenc, 2017), in which we compared attitudes toward inclusion between pedagogical professionals and volunteers. The study indicated that, to some extent, volunteers expressed more positive attitudes about inclusion compared with the trained professionals, who does not need to focus on supporting students in achieving prescribed learning outcomes instead of considering also other dimension of their inclusion.…”
Section: Discussionmentioning
confidence: 52%